2017
DOI: 10.1101/141010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inferring Functional Neural Connectivity with Deep Residual Convolutional Networks

Abstract: Measuring synaptic connectivity in large neuronal populations remains a major goal of modern neuroscience. While this connectivity is traditionally revealed by anatomical methods such as electron microscopy, an efficient alternative is to computationally infer functional connectivity from recordings of neural activity. However, these statistical techniques still require further refinement before they can be reliably applied to real data. Here, we report significant improvements to a deep learning method for fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Our experiments showed that unsupervised learning provides a more efficient solution. However, we know that RCNN has the strongest solution with networks of 1000 cells [6] and as we showed, it has a very competitive performance even with networks of 100 cells. Thus, the use of supervised methods can be justified, if certain requirements regarding the computational resources and the volume of data are satisfied.…”
Section: Future Workmentioning
confidence: 73%
See 2 more Smart Citations
“…Our experiments showed that unsupervised learning provides a more efficient solution. However, we know that RCNN has the strongest solution with networks of 1000 cells [6] and as we showed, it has a very competitive performance even with networks of 100 cells. Thus, the use of supervised methods can be justified, if certain requirements regarding the computational resources and the volume of data are satisfied.…”
Section: Future Workmentioning
confidence: 73%
“…However, there is not extensive literature based on neural networks for network inference and analysis, with small exceptions, such as a convolutional neural network that identifies contrastive underlying weighted network structures in fMRI data of different subject groups [17]. In this work, we are going to examine a residual convolutional neural network, which is based on the method that achieved fourth place in the competition [28] and has been extended to a state of the art solution [6]. This method is accompanied with its own preprocessing, as the model works directly with the fluorescence signals.…”
Section: Residual Convolutional Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation